A validation study of the final ratings in predicting students' achievement in SEDP mathematics III. - Aragon, Aurelia Rhodora U. (Animo Repository, 1995)
The study examines the reliability of the final ratings used in the Career Streaming Classification Scheme as a basis for placing incoming third year students to specific career sections in their junior year. Specifically, the study establishes the predictive validity of the ratings in predicting students achievement in SEDP Mathematics III. The subjects were 101 high school students of San Beda College comprising three different career sections under one Mathematics teacher. The first quarter (Q1) grades of the students in Mathematics III were correlated with the students' final rating in the streaming program. The result of the z-test, at the .05 level of significance, indicate that the final rating is significantly related to the Q1 Mathematics grade. Z-test results also showed that the differences in correlation coefficients were not significant. This means that the Q1 grades in Mathematics III correlated significantly with the final rating obtained from any of the three career sections. T-test results (p < .05) further proved that the students of the Engineering (ENGR) class were more proficient in Mathematics than the students of other career sections. However, it was found through regression analysis that the final rating for the ENGR class, though contributing the least to the Mathematics grade, is not significantly different from the other predicted grades.